Global intercomparison of functional pyrodiversity from two satellite sensors. Issue 24 (17th December 2021) - Moreno, M. Vanesa; Laurent, Pierre; Mouillot, Florent
ABSTRACT: Fires create substantial ecosystem disturbances, which affect biodiversity and climate processes. Previously, satellite-derived burned areas were assessed, and fire patches and morphological traits related to fire spread functions identified. The cut-off value in days is a critical parameter for the algorithms used to identify fire patches, as it identifies when two contiguous burned pixels should be grouped together as one patch. Our understanding of how fire patches and their morphologies change with the cut-off values between satellite sensors is currently insufficient for model development and pyrogeographic studies. We have addressed this using the FRY v1.0 global database of fire patch functional traits, with cut-off values of 3, 5, 9, and 14 days, derived from two burned area products, the MERIS Fire_cci version 4.1 and MODIS MCD64A1 collection 6, from two satellite sensors with different spatial and temporal resolutions. We intercompared the FRY products with functional diversity trait methods that assess their morphological pyrodiversity structures and dissimilarities. We have assessed the functional pyrodiversity of the FRY products with four cut-off values, for fire patches ≥ 300 ha, on 1° resolution tiles for the world and Global Fire Emissions Database (GFED) region scales, from 2005–2011. The functional structures and dissimilarities between the FRY products varied with the regions, while cut-off value sensitivity varied with the regions and between the satellite sensor products. These variations in functional structures and dissimilarities mirrored the regional fire spread processes and satellite sensor resolutions. The functional pyrodiversity that varied with the regions and similar cut-off values did not lead to the best agreement between the satellite sensor products. These variations reinforce the need to combine high temporal resolution optical sensors with radar in tropical regions, to consistently meet the monitoring requirements and for international organizations, to enable improved assessments of climate and biodiversity.